GAMBARAN PENGGUNA KOMPONEN THROMBOCYTE CONCENTRATE (TC) DI UTD PMI KABUPATEN SLEMAN TAHUN 2019 - Francisca Romana Sri Supadmi (Jurnal Ilmiah Cerebral Medika, 2021)
The rampant spread of dengue fever in 2019 in Sleman that reached 728 cases caused the need for the Thrombocyte Concentrate (TC) component in Indonesian Red Cross Distric Sleman increased to 215 TC bags. This number escalated highly than the previous years. The purpose of the study was to figure out the profiles of TC component users in Indonesian Red Cross Distric Sleman in 2019, with the covered characteristics such as sex, age, blood type, and indication. The study design used a non-participant observational method with retrospective design. The samples were 67 recipients who directly requested TC component to Indonesian Red Cross Distric Sleman in 2019. The choosing of samples with a total sampling technique. The result showed that most of the recipients who directly requested TC component to Indonesian Red Cross Distric Sleman in 2019 were female (46 recipients), mostly were teens (23 recipients) and young adults (16 recipients), had O rhesus positive blood type (45 recipients) and indicated with dengue fever. The profiles of TC component user in Indonesian Red Cross Distric Sleman in 2019 were mostly females, aged around 12-35 years old, had O rhesus positive blood type with dengue fever indication.